PAX8 EXPRESSION AND ITS ASSOCIATIONS IN PRIMARY RENAL CELL CARCINOMA: A CROSS SECTIONAL STUDY - Ahmed Zamir (Army Medical College Rawalpindi, 2021)
Objective: To determine the frequency of PAX8 expression in cases of primary renal cell carcinoma (RCC) and its association with patient demographics and tumor type.